Islamic Education Movie: Character Learning Through Nussa-Rara Movie - Fathayatul Husna; Ratna Sari Dewi (Universitas Muhammadiyah Yogyakarta, 2021)
This article examines the Islamic cartoon film Nussa and Rara. The author used Nussa and Rara as a window to see the emergence of Islamic cartoon films. Its strengths are in conveying educational values to children and as a learning medium to build character education for children aged 12 years and under. To explain this phenomenon, the author employed the content analysis method and combined it with relevant data; those were strengthened by many research results and literature studies. Through this method, the author showed that Nussa and Rara movie shares Islamic value in each segment, such as the value of honesty, asking for prayers on time, respecting neighbors, and so on. The author tried to see how every figure, especially Umma as Nussa and Rara’s mother, explains and exemplifies how to be a good Muslim. Through this article, it could be concluded that films are not always judged to have a negative impact on the audience. Even films can contribute as a medium for education and dissemination of Islamic da'wah. Besides, through films, it can also contribute to building good character for children under 12 years of age. Some learning methods that can be used are the many steps or methods that can be planted in children, such as the habituation and storytelling methods. These methods can be used to apply the values of faith, moral values, and worship values. Thus, this article greatly contributes to enriching academic discourse related to character learning for children under 12 years of age. This article concluded that the Nussa and Rara cartoon film really strives to spread Islamic da'wah and build children's character from an early age with daily customs and begin to familiarize children to apply the values of Islamic teachings perfectly.